2012
DOI: 10.1038/ncb2466
|View full text |Cite|
|
Sign up to set email alerts
|

Telomeric DNA damage is irreparable and causes persistent DNA-damage-response activation

Abstract: The DNA damage response (DDR) arrests cell-cycle progression until damage is removed. DNA damage-induced cellular senescence is associated with persistent DDR. The molecular bases that distinguish transient from persistent DDR are unknown. Here we show that a large fraction of exogenously-induced persistent DDR markers are associated with telomeric DNA in cultured cells and mammalian tissues. In yeast, a chromosomal DNA double-strand break (DSB) next to telomeric sequences resists repair and impairs DNA ligase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

33
647
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 694 publications
(701 citation statements)
references
References 55 publications
33
647
2
Order By: Relevance
“…However, since not all cells with DDR foci expressed high levels of α‐SMA in stress fibers (Supporting Information Figure S3d), our data also suggested that activation of the DDR alone is not sufficient for myofibroblast transdifferentiation and that other factors, such as timing of DDR induction or long‐term persistence of the DDR, are critical for activating the transdifferentiation program. As dysfunctional telomeres activate a persistent DDR while nontelomeric DSBs are repaired within minutes of being generated (Fumagalli et al, 2012; Hewitt et al, 2012), we tested whether fibroblasts are stimulated to transdifferentiate preferentially due to a persistent telomeric DDR. By simultaneously immunostaining TGF‐β1‐treated cells for α‐SMA expression and TIF formation, we discovered that the great majority of α‐SMA‐expressing myofibroblasts indeed displayed dysfunctional telomeres and were TIF positive (75%).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, since not all cells with DDR foci expressed high levels of α‐SMA in stress fibers (Supporting Information Figure S3d), our data also suggested that activation of the DDR alone is not sufficient for myofibroblast transdifferentiation and that other factors, such as timing of DDR induction or long‐term persistence of the DDR, are critical for activating the transdifferentiation program. As dysfunctional telomeres activate a persistent DDR while nontelomeric DSBs are repaired within minutes of being generated (Fumagalli et al, 2012; Hewitt et al, 2012), we tested whether fibroblasts are stimulated to transdifferentiate preferentially due to a persistent telomeric DDR. By simultaneously immunostaining TGF‐β1‐treated cells for α‐SMA expression and TIF formation, we discovered that the great majority of α‐SMA‐expressing myofibroblasts indeed displayed dysfunctional telomeres and were TIF positive (75%).…”
Section: Resultsmentioning
confidence: 99%
“…Significantly, telomere dysfunction‐induced senescence (TDIS) can also be triggered in the absence of continuous cell proliferation and in the absence of critical telomere shortening. For example, genotoxic stresses that cause DSB formation in telomeric repeats can rapidly activate TDIS, as telomeric breaks resist DNA repair activities (Fumagalli et al, 2012; Hewitt et al, 2012; Suram et al, 2012). Stresses that have been demonstrated to cause TDIS include oncogene expression (Patel, Suram, Mirani, Bischof, & Herbig, 2016; Suram et al, 2012), DNA replication stress (Boccardi et al, 2015; Fumagalli et al, 2012; Hewitt et al, 2012), and reactive oxygen species (ROS) (Boccardi et al, 2015), among others.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although most DSBs in arrested cells are eventually resolved by cellular DSB repair processes, some persist and consequently convert the otherwise transient DDR into a more permanent growth arrest. We and others have demonstrated that the persistent DDR is primarily telomeric, triggered by irreparable telomeric DSBs (1,10,11).…”
mentioning
confidence: 99%
“…The main mediators of DNA damage response are the DNA damage kinases ATM, ATR, CHK1, and CHK2, which phosphorylate and activate several cell cycle proteins, including p53 (Campisi and d'Adda di Fagagna 2007). Moreover, phosphorylated p53 protein activates the expression of p21, which binds to and inhibits some CDKcyclin complexes, particularly those involving CDK2, finally altering the proliferative activity of cells (Fumagalli et al 2012). Both cell proliferation and differentiation are striking features of the new tissue formation phase, and several markers and morphologic features characterize senescent cells.…”
Section: Cell Proliferationmentioning
confidence: 99%